PENERAPAN SUPERVISI AKADEMIK DALAM PENGELOLAAN KURIKULUM OLEH KEPALA SEKOLAH DI SD DARUSSALAM BLOKAGUNG - Wahyudi, Moh. Imam (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
The purpose of this study is to analyze in depth how principals implement academic supervision in curriculum management at SD Darussalam Blokagung. This study uses a qualitative case study approach with the location at SD Darussalam Blokagung, which was selected purposively because it integrates the national curriculum and Islamic values. Data was collected through in-depth interviews, participatory observation, and documentation, with subjects including the principal, teachers, and curriculum staff. Data analysis was conducted interactively through reduction, presentation, and conclusion drawing. Triangulation techniques were used to test the validity of the data. This study aims to understand academic supervision strategies and their impact on curriculum management in the context of pesantren-based education. The results of this study show that the implementation of academic supervision by the principal at SD Darussalam Blokagung has distinctive characteristics, namely being based on Islamic values, being transformational, and being able to harmoniously integrate the national curriculum and pesantren curriculum. This supervision does not only focus on technical aspects but also nurtures teachers' moral, spiritual, and professional development. This approach fosters a religious and collaborative school culture. These findings indicate that value-based supervision is highly relevant for implementation in Islamic boarding school-based schools and can serve as a model for developing more contextual, humanistic, and visionary academic leadership.